Prevalence of Urinary Tract Infection among Children - a cross-sectional study in Arar city, Northern Border Area, KSA - Shehab Ahmed Alenazi, Sarwar Hussain, Amir Fayyaz, Ekramy Elmorsy, Irfan Hanif, Sowsan Hassan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Urinary tract infection (UTI) is one of the most common infections in children. The prevalence of UTI during childhood varies by gender, age, and multiple other factors. The most commonly causes of UTI in children are E. coli and Klebsiella in different parts of the world. Aim: To evaluate the prevalence of UTI, its etiologic pathogens, presenting symptoms and probable risk factors in our area. Methods; A retrospective cross-sectional study was conducted on electronic files of 606 pediatric participants of confirmed UTIs from year 2015 -2020 in arar city hospital. These cases were diagnosed after urine culture positive for the respected uropathogens. Urine samples were collected either transurethral in < 1year children and clean voided midstream in elder children under aseptic techniques. The samples were sent to the hospital lab with especial request that we would use these samples for our study. Hospital laboratory followed full protocol that is followed worldwide. Results: Total of 606 confirmed cases of UTI were used. Of this, 370(61.05%) were females and 236 (38.94%) males. Among them, 253 (41.74%) were <1 year old, 229(37.78%) were 1–5-year-old whereas 124(20.46%) were above 5 years old children. We found that E. coli was the most prevalent organism 342(56.23%), followed by Klebsiella which was 175(28.8%). E. coli was more common in outpatients compared to Klebsiella which was the most common aetiologic agent isolated from hospital admitted patients. Citrobacter, Enterococci, Actinobacteria and Pseudomonas aeruginosa were commoner in hospital patients. High grade fever, dysuria and foul smelling was the main symptom of E. coli positive cases whereas foul smelling was common in Klebsiella positive cultures. Constipation was noted to be the most common 198(32.6%) risk factor in our area. Other risk factors were history of instrumentation, history of catheterization, structural abnormalities, and posterior urethral valve abnormalities which were 9.9 %, 9.9 %, 10.2% and 3.30% respectively. Conclusion: We conclude first; Prevalence of UTI was more common in females than males in < 1 year old group. Second; E.coli was the most common bacteria followed by Klebsiella. Third; it showed that along with other risk factors, constipation plays a significant role in causation of UTI in our area. Keywords; UTI, children, risk factors